2005
DOI: 10.1074/jbc.m411217200
|View full text |Cite
|
Sign up to set email alerts
|

HDQ (1-Hydroxy-2-dodecyl-4(1H)quinolone), a High Affinity Inhibitor for Mitochondrial Alternative NADH Dehydrogenase

Abstract: Alternative NADH dehydrogenases (NADH:ubiquinone oxidoreductases) are single subunit respiratory chain enzymes found in plant and fungal mitochondria and in many bacteria. It is unclear how these peripheral membrane proteins interact with their hydrophobic substrate ubiquinone. Known inhibitors of alternative NADH dehydrogenases bind with rather low affinities. We have identified 1-hydroxy-2-dodecyl-4(1H)quinolone as a high affinity inhibitor of alternative NADH dehydrogenase from Yarrowia lipolytica. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 24 publications
2
67
0
Order By: Relevance
“…2). This result implies that exogenously bound UQ 6 is not bound to exactly the same site as endogenously bound UQ 8 . Moreover, these results suggest that Ndi1 forms a ternary complex with NADH and UQ in close vicinity of FAD and that UQ can withdraw an electron from reduced flavin, leading to the formation of the CT complex.…”
Section: Purification Of Uq-bound Ndi1-mentioning
confidence: 80%
See 4 more Smart Citations
“…2). This result implies that exogenously bound UQ 6 is not bound to exactly the same site as endogenously bound UQ 8 . Moreover, these results suggest that Ndi1 forms a ternary complex with NADH and UQ in close vicinity of FAD and that UQ can withdraw an electron from reduced flavin, leading to the formation of the CT complex.…”
Section: Purification Of Uq-bound Ndi1-mentioning
confidence: 80%
“…Indeed, the NADH binding site of the group A family of NDH-2 enzymes has been suggested to exist near the FAD binding site (2,20). In the case of NDH-2 from Yarrowia lipolytica, it was suggested that NADH and the quinone head group interact with the same binding pocket competitively (8). To obtain an understanding of the structure of the binding sites of the substrates in Ndi1, we referred to the x-ray crystal structures of other flavin enzymes: thioredoxin reductase of Drosophila melanogaster (DmTR) (21) and lipoamide dehydrogenase of Pseudomonas putida (PpLipDH) (22).…”
Section: Purification Of Uq-bound Ndi1-mentioning
confidence: 99%
See 3 more Smart Citations